Financial Performance : The Role of Management Ability and CSR Disclosure with CEO Tenure as Moderator - Bonita Prabasari; Adhi Pradiptya; Rahma Prafinta Sari; Daniel Teguh (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of managerial ability and Corporate Social Responsibility (CSR) on financial performance, while the moderating role of CEO tenure. Superior managerial ability manifests as a CEO’s capability to allocate resources efficiently, execute strategic decisions, and mitigate operational risks. Concurrently, CSR is recognized as a strategic instrument to build corporate legitimacy, enhance reputation, and foster long-term stakeholder relationships, which are theorized to improve financial outcomes. Despite these theoretical foundations, previous empirical findings remain inconsistent. This research proposes CEO tenure as a potential moderating factor, grounded in the premise that a longer tenure provides executives with deeper organizational insight and broader networks to optimize the impact of managerial skills and social initiatives. The research focuses on the basic materials sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This study utilizes secondary data obtained from audited annual reports and sustainability reports. Data analysis was conducted using panel data regression via EViews software. The empirical results demonstrate that managerial ability exerts a significant positive influence on financial performance, confirming that executive efficiency is a critical driver of corporate profitability within the sector. Conversely, CSR disclosure was found to have no significant effect on financial performance, suggesting that social responsibility initiatives may not be viewed as primary determinants of financial value by investors in the Indonesian basic materials industry during the observation period. Furthermore, the results indicate that CEO tenure fails to moderate the relationship between either managerial ability or CSR disclosure and financial performance. These findings imply that the efficacy of a CEO’s capability and social policies remains independent of their length of service. This study contributes to the strategic management literature by clarifying the internal drivers of performance in a volatile market context.